Book Review: The Apostolic Fathers and the New Testament - Chandra Gunawan (Cipanas Theological Seminary, 2022)
In The Apostolic Fathers and the New Testament, Clayton addresses five issues, namely, the historical setting of the church father literature, the genre and setting in life of the church father literature, the ethics, and faith in the church father teaching, the struggle of the church fathers concerning the opposition from the Jewish and Gentile society, the influence of some churches in the second century. After observing the historical setting of church fathers, Jefford concludes that the letter of Ignatius was written ca., 107-109 AD from Asia Minor; the letter of Polycarp was written ca., 108-109 AD from Smyrna; 1 Clement was written ca., 65-70 AD from Rome; the Didache was written ca., 120 AD from Antioch; the Martyrdom of Polycarp was written ca., 155-160 AD from Smyrna; the Shepherd of Hermas was written ca., 90-150 from Rome; 2 Clement was written c.a. 166-174 from Corinthians; the letter of Barnabas was written ca., 96-100 from Alexandria; the Epistle of Diognetus could be composed around the first to the third century from anywhere around the Mediterranean world; the lost written work of Papias, Exposition of the Oracle of the Lord, probably was written in 130 AD.